2003
DOI: 10.1557/proc-792-r9.2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Patterning of GaSb Surfaces with Br-IBAE for Antimonide Based Molecular Beam Epitaxy

Abstract: Bromine Ion Beam Assisted Etching (Br-IBAE) is shown to be useful in removing GaSb wafer chemical mechanical polish (CMP) surface and subsurface damage; creating microstructure patterns in GaSb surfaces through stencil, photoresist, and oxides masks; and stabilizing the as-etched GaSb surface with a thin, easily thermally desorbed oxide layer. Thus, the Br-IBAE technique is well suited as a GaSb surface final-polish technique in overgrowth applications that require “epi-ready” GaSb (100) surfaces for molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The substrate-film transition for Br-IBAE finished GaSb substrates showed a smooth, defect-free transition with no discernable interface. 7 However, due to the increased surface roughness of the surface template, there was simultaneous growth along several crystal planes and thus the films did not benefit from selfplanarizing. Epitaxial growth at lower substrate temperatures has been suggested in the literature to improve episurface quality.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The substrate-film transition for Br-IBAE finished GaSb substrates showed a smooth, defect-free transition with no discernable interface. 7 However, due to the increased surface roughness of the surface template, there was simultaneous growth along several crystal planes and thus the films did not benefit from selfplanarizing. Epitaxial growth at lower substrate temperatures has been suggested in the literature to improve episurface quality.…”
Section: Results and Analysismentioning
confidence: 99%
“…Several wet etch techniques have been developed to prepare GaSb surfaces for epitaxial growth with varying degrees of success. 3 Recently, dry-etch techniques using the gas-cluster ion beam (GCIB) 4,5,6 technique, incorporating either O 2 or CF 4 /O 2 as the source gas, and the bromine ion-beam assisted etching (Br-IBAE) 7 technique have been successfully implemented as surface preparation methods for molecular beam epitaxy (MBE). Here, a measurement of rms roughness (R rms ) and maximum peak-to-valley heights (∆Z) showed that the chosen GCIB processes consistently smoothed GaSb surfaces while the Br-IBAE process produced rougher surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The substrates were then GCIB and Br-IBAE processed, details of which can be found in Refs. [11,12], respectively. The process parameters employed were as follows:…”
Section: Surface Treatment Of Gasbmentioning
confidence: 99%
“…Epitaxial growth on GCIB processed substrates showed improved substrate/epi interfaces, when compared to CMP surfaces, with the presence of a dislocation layers that was attributed to incomplete oxide desorbtion [11]. An alternate surface preparation method using Br-ion beamassisted etching (Br-IBAE) was also implemented [12]. Though the Br-IBAE process increased surface roughness of the GaSb substrates, epitaxial growth showed smooth, dislocation-free substrate-to-epi transitions with no discernable interface, attributed to complete oxide desorption.…”
Section: Introductionmentioning
confidence: 99%